A RELAÇÃO ESCOLA - FAMÍLIA: UM ESPAÇO NEGADO AOS PAIS? - Levino Bertan (Universidade do Oeste Paulista, 2005)
This text presents some reflections about the space that the family has in the public state and city schools. The school invites the family to be a partner but actually this only opens space to complains, embarrassments and help requests to solve problems with a specific subject. This becomes evident with the results of the observations and interviews with parents and teachers who live this problem and do not find a satisfactory way out of it, leading to a question: what can be done to change this situation? The meetings are necessary to gather partners and not to embarrass them. The participation of all is fundamental. And this participation cannot be mistaken with a simple involvement of the ones present at the meeting. To participate is to take part, to get in opening doors, exchanging services, dialogue, love, and thus assuming an intervation in the reality and trying to change it.